Variants of SARS-CoV-2: Influences on the Vaccines’ Effectiveness and Possible Strategies to Overcome Their Consequences - Ali A. Rabaan; Shamsah H. Al-Ahmed; Hawra Albayat; Sara Alwarthan; Mashael Alhajri; Mustafa A. Najim; Bashayer M. AlShehail; Wasl Al-Adsani; Ali Alghadeer; Wesam A. Abduljabbar; Nouf Alotaibi; Jameela Alsalman; et al. (Medicina, 2023)
The immune response elicited by the current COVID-19 vaccinations declines with time, especially among the immunocompromised population. Furthermore, the emergence of novel SARS-CoV-2 variants, particularly the Omicron variant, has raised serious concerns about the efficacy of currently available vaccines in protecting the most vulnerable people. Several studies have reported that vaccinated people get breakthrough infections amid COVID-19 cases. So far, five variants of concern (VOCs) have been reported, resulting in successive waves of infection. These variants have shown a variable amount of resistance towards the neutralising antibodies (nAbs) elicited either through natural infection or the vaccination. The spike (S) protein, membrane (M) protein, and envelope (E) protein on the viral surface envelope and the N-nucleocapsid protein in the core of the ribonucleoprotein are the major structural vaccine target proteins against COVID-19. Among these targets, S Protein has been extensively exploited to generate effective vaccines against COVID-19. Hence, amid the emergence of novel variants of SARS-CoV-2, we have discussed their impact on currently available vaccines. We have also discussed the potential roles of S Protein in the development of novel vaccination approaches to contain the negative consequences of the variants’ emergence and acquisition of mutations in the S Protein of SARS-CoV-2. Moreover, the implications of SARS-CoV-2’s structural proteins were also discussed in terms of their variable potential to elicit an effective amount of immune response.